Policy Analysis of New Autonomous Region Formation: A Case Study on the Readiness of Tondano City Formation Based on Government Regulation Number 78 of 2007 - Brillyant Virechely Tarore; Abdul Hakim; Hermawan - (Faculty of Law, Universitas Pekalongan, 2023)
This research aims to describe and analyze the implementation of Government Regulation Number 78 of 2007, focusing on the supporting and inhibiting factors in the process of preparing Tondano Raya District to become Tondano City, a New Autonomous Region. Using the Policy Analysis theory by Patton & Sawicki (2012), the study develops policy alternatives to ensure readiness for this transformation. The findings indicate that while there is significant community support for forming Tondano City, several administrative and technical requirements stipulated by Government Regulation Number 78 of 2007 remain unmet. Specifically, administrative challenges, economic indicators, and infrastructure improvements are needed. High community support and abundant natural resources are major supporting factors, yet the lack of clear regulations and a moratorium policy present significant obstacles. The proposed policy alternatives include: strengthening relationships between the DPR and the community, completing and updating essential data, maintaining population quality and quantity, increasing Profit Sharing Funds, General Allocation Funds, and Special Allocation Funds, enhancing local revenue policies, adjusting expenditure patterns, securing potential national financial sources for local management, granting greater discretion to local governments, promoting industrial development, and optimizing resource potential in the prospective new autonomous region. These alternatives aim to comprehensively address the readiness for the future formation of Tondano City as a New Autonomous Region, ensuring sustainable development and improved public services. Keywords:policy analysis; formation of new autonomous regions; policy alternatives